Stabilisasi Tanah Lempung Desa Tumbang Rungan dengan Roadbooster untuk Perkerasan Jalan - Evi Meilisa Adhanty; Rida Respati; Norseta Ajie Saputra (Media Ilmiah Teknik Sipil, 2017)
Land is the foundation for construction. Foundation is the lowest part of a construction, serves to channel the load directly from the construction structure to the soil layer at underneath it. Soils that have bad properties are very unfavorable if used for something construction, especially for highway pavement. The way to increase the carrying capacity of clay soil is to do soil stabilization efforts, that is, using roadbooster as a stabilizing chemical and is expected to improve the nature of the clay and meets the requirements for road pavement materials. In this study will stabilization of the clay soil of Tumbang Rungan Village Palangka Raya with the main parameters which is used as a research reference, namely California Bearing Ratio (CBR) immersion and Unconfined Compressive Strength (UCS). Based on the results of testing the clay soil of Tumbang Rungan Village, Palangka Raya, the data were obtained: Original ground immersion CBR 7.89%, CBR immersion 0% roadbooster 76%, CBR 4% immersion roadbooster 40.85%, CBR immersion 8% roadbooster 27.08%, UCS original soil 0.56 kg / cm2, UCS 0% roadbooster 7.30 kg / cm2, UCS 4% roadbooster 7.40 kg / cm2, and UCS 8% roadbooster 8.30 kg / cm2. From the CBR data, you can see the value The highest CBR is when mixing 0% roadbooster or without additional roadbooster, while the highest UCS value lies in mixing 8% roadbooster.